Down-regulation of the insulin signaling pathway by SHC may correlate with congenital heart disease in Chinese populations. (4th February 2020) - Luo, Zhiling; Xu, Longjiang; Lu, Jiang; Shen, Yan; Tang, Yongyan; Wang, Xiuyun; Wu, Yilin; Sun, Hao; Guo, Tao
Abstract: Background/Aims: Congenital heart disease (CHD) is one of the most common and severe congenital defects. The incidence of fetal cardiac malformation is increased in the context of maternal gestational diabetes mellitus (GDM). Therefore, we wanted to determine whether abnormalities in the insulin signaling pathway are associated with the occurrence of nonsyndromic CHD (ns-CHD). Methods: We used digital gene expression profiling (DGE) of right atrial myocardial tissue samples from eight ns-CHD patients and four controls. The genes potentially associated with CHD were validated by real-time fluorescence quantitative PCR analysis of right atrial myocardial tissues from 37 patients and 10 controls and the H9C2 cell line. Results: The results showed that the insulin signaling pathway, which is mediated by the SHC gene family, was inhibited in the ns-CHD patients. The expression levels of five genes ( PTPRF, SHC4, MAP2K2, MKNK2, and ELK1 ) in the pathway were significantly down-regulated in the patients' atrial tissues ( P <0.05 for all). In vitro, the H9C2 cells cultured in high glucose (33 mmol/l) expressed less SHC4, MAP2K2, and Elk-1 than those cultured in low glucose (25 mmol/l). Furthermore, the high glucose concentration down-regulated the 25 genes associated with blood vessel development based on Gene Ontology (GO) term enrichment analyses of RNA-seq data. Conclusion: We considered that changes in the insulin signaling pathway mediated by SHC might be involved in the heart development process. This mechanism might account for the increase in the incidence of fetal cardiac malformations in the context of GDM.